WORD FORMATIONS OF JARGON USED IN THE US MILITARY IN THE EXPENDABLES 3 MOVIE - Sastika Seli (Universitas Sarjanawiyata Tamansiswa, 2019)
The present study aims to describe the form, function and the word formation of US military jargon in â€œThe Expendables 3â€ movie. Data collection was administered through movie observation and orthographic transcription. Data analysis was administered through identification, data reduction, classification and description. The results reveal 4 forms of jargon based on the word class including jargon in word forms, phrases forms, abbreviation and acronym with word forms jargon as the highest frequency of use. The second frequency of usage is jargon in phrase form which occurs in 12 phrases. Abbreviation occurs only in 2 forms and acronym occurs in 1 usage. US military jargon in the movie has 3 functions: to show the identity of the group, to strengthen the intimacy among the users in group and to show that someone is mastering the skill in military. The last finding of word formation presents 9 jargon formations and two of them indicate two combinations of two word formations and most of jargons are formed by borrowing.